2011
DOI: 10.5577/intdentres.2011.vol1.no2.2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Three Different Application Times of 17% EDTA and 7% Maleic Acid Irrigation Agents on the Removal of Debris and Smear Layer: A Scanning Electron Microscope Study

Abstract: Aim: This study compared smear-layer and debris removal using with three different application times of 17% EDTA and 7% maleic acid irrigation agents. Methodology: Fifty-two maxillary and mandibular single-rooted teeth were divided randomly into seven groups (n = 8 each, control group n = 4). Three groups received 17% EDTA and three received maleic acid (1, 5, 10 min). Canals were prepared using nickel-titanium rotary files. Smear-layer and debris removal were evaluated in the coronal, middle, and apical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…A previous study has shown that conventional needle irrigation delivered irrigating solution only 1 mm deeper than the tip of the needle (31). Removal of the smear layer and debris is more readily accomplished in the cervical and middle thirds of root canals than in the less-accessible apical third (19,32,33,34). Effective irrigation of the canal is essential in the critical the apical area during rootcanal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that conventional needle irrigation delivered irrigating solution only 1 mm deeper than the tip of the needle (31). Removal of the smear layer and debris is more readily accomplished in the cervical and middle thirds of root canals than in the less-accessible apical third (19,32,33,34). Effective irrigation of the canal is essential in the critical the apical area during rootcanal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Re-incorporation of teeth with previous endodontic treatment and excessive substance loss may be possible using posts inserted into the root canal, which assist retention of the restoration [ 1 3 ]. Debridement during root canal treatment is mandatory and is a major element of endodontic success [ 4 9 ]. Lasers can be used to produce dentin surfaces suitable for bonding of adhesive resin cement.…”
Section: Introductionmentioning
confidence: 99%